2009
DOI: 10.1590/s0100-06832009000600029
|View full text |Cite
|
Sign up to set email alerts
|

Erosividade da chuva e erodibilidade de Cambissolo e Latossolo na região de Lavras, sul de Minas Gerais

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2
31

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 15 publications
2
28
2
31
Order By: Relevance
“…The lowest losses, coinciding with the lowest rainfall and erosivity levels determined during the experimental period, were observed in February. Several authors report that the highest soil and water losses occur in December, due to high rainfall and erosivity in the central region of Brazil (CARVALHO et al, 2009;SILVA et al, 2009;SILVA et al, 2010), which was not confirmed here, probably due to the more effective plant cover. The total losses of soil and water showed the following trend: bare soil > millet under downslope tillage > millet under contour seeding> pigeon pea under downslope tillage > jack bean under downslope tillage > pigeon pea under contour seeding > jack bean under contour seeding (Table 4).…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…The lowest losses, coinciding with the lowest rainfall and erosivity levels determined during the experimental period, were observed in February. Several authors report that the highest soil and water losses occur in December, due to high rainfall and erosivity in the central region of Brazil (CARVALHO et al, 2009;SILVA et al, 2009;SILVA et al, 2010), which was not confirmed here, probably due to the more effective plant cover. The total losses of soil and water showed the following trend: bare soil > millet under downslope tillage > millet under contour seeding> pigeon pea under downslope tillage > jack bean under downslope tillage > pigeon pea under contour seeding > jack bean under contour seeding (Table 4).…”
Section: Resultscontrasting
confidence: 51%
“…When studying how agroforestry systems reduce the intensity of erosive agents, Aguiar et al (2006) observed that sediments and water losses were concentrated during the end of the rainy period, due to the previous soil moisture. Silva et al (2009) concluded that the highest risks related to water erosion occur between November and March, due to the greater rainfall erosive potential and the preceding soil moisture.…”
Section: Resultsmentioning
confidence: 99%
“…Bi: horizon B incipient; Bw: horizon B weathering. Source: Silva et al (2009 (6) Soil loss (%) represents soil loss for each rainfall pattern divided by total soil loss, multiplied by 100; (7) Soil loss per rainfall event (Mg ha -1 ) represents soil loss in each rainfall pattern divided by the number of erosive rainfall events. differed between CXbd and LVdf (39.1 and 1.8 Mg ha -1 soil loss from CXbd and LVdf, respectively), for the same rainfall event with only 4 h duration and an erosive potential of 1,663 MJ mm ha -1 h -1 (EI 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…These examples demonstrate the need to obtain the best correlation between soil losses and the variables that constitute the rainfall erosivity index (EI 30 ), which is hampered by the limited knowledge on rainfall physical characteristics, since soil losses are related not only to their erosive potential, but also to the location of the highest peak intensity, the moisture antecedent to the rainfall and also the moisture antecedent to the peak intensity Loyola & Prevedello, 2003;Silva et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation